Fast‐activated anionic polymerization of ε‐caprolactam in the bulk under quasi‐adiabatic conditions: Comparison of different kinetic models. Issue 20 (23rd July 2013) - Russo, Saverio; Maniscalco, Sabrina; Moretti, Paolo; Ricco, Laura
ABSTRACT The kinetics of ε‐caprolactam fast‐activated anionic polymerization in the bulk under quasi‐adiabatic conditions is analyzed in terms of three semiempirical schemes. Malkin's model, the most frequently quoted approach in the literature, provides an excellent simulation of the polymerization kinetics in our experimental conditions, but the values of the derived parameters do not remain constant, as predicted by the model when different experimental conditions are chosen, and do not allow any correlation with the physical and chemical aspects of the reaction. The same limit exists for Lin's model, with a poorer agreement between simulation and experimental data. Only Kamal–Sourour's model provides almost constant values of the parameters present in the equation and can be considered a valid approach for the description of the whole course of the reaction in our experimental conditions. The relevance of the auto acceleration step is compared for two very fast activators and related to the most accredited interpretation of its occurrence. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4474–4480